Microplastic Pollution in Urban Water Systems, Environmental and Public Health Implications: A Narrative Review - Pitriani (Yayasan Sinergi Kawula Muda, 2024)
Microplastic contamination in urban water systems is a growing concern due to its ecological and health impacts. This review explores the sources, transport mechanisms, and public health implications of microplastics in urban water systems. A systematic review was conducted using PubMed, Scopus, and Google Scholar, targeting peer reviewed articles from the last decade. Selection criteria emphasized studies linking plastic pollution to water quality and human health. Microplastics are prevalent in urban rivers, lakes, and wastewater treatment plants, with concentrations varying by region and waste management practices. Key sources include single use plastics, urban runoff, and ineffective filtration in treatment plants. Human exposure occurs through drinking water and food consumption, with potential risks such as endocrine disruption and toxic bioaccumulation.Effective mitigation requires integrated approaches including advanced treatment technologies, stricter regulations, and public engagement. Further research should address detection standardization and long term health risks.